Method for preparing hydrothermal carbon material from chlorine-containing plastic or rubber and application of hydrothermal carbon material

The microwave method assists in hydrothermal treatment of waste chlorine-containing plastics, which solves the problem of recycling carbon species and chloride ions, achieves rapid and efficient degradation and excellent photocatalytic and adsorption properties, and avoids environmental pollution.

CN119612484APending Publication Date: 2025-03-14NORTHWEST UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411706668.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The prior art is difficult to effectively recycle carbon species and chloride ions in waste chlorine-containing plastics or rubbers, and lead to environmental pollution during landfill and incineration.

Method used

The microwave method assists in rapid hydrothermal treatment of waste chlorine-containing plastics, and the hydrothermal carbon materials are prepared and chloride ions are recovered by ultrasonic dispersion in a closed container and hydrothermal treatment in a microwave high-pressure reactor.

Benefits of technology

The rapid and efficient degradation of waste chlorine-containing plastics is achieved, the release of toxic gases during the pyrolysis process is avoided, and hydrothermal carbon materials with excellent photocatalytic and adsorption properties are prepared.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a method for preparing a hydrothermal carbon material by using chlorine-containing plastic or rubber and application of the hydrothermal carbon material, and the preparation method comprises the following steps: dispersing waste chlorine-containing plastic or rubber in water in a closed container, and performing hydrothermal treatment in a microwave reactor to obtain a hydrochloric acid aqueous solution and the hydrothermal carbon material. The hydrothermal carbon material can be used as a photocatalyst applied to preparation of hydrogen peroxide through oxygen reduction, hydrogen evolution through water reduction and preparation of carbon monoxide through photocatalytic carbon dioxide reduction, and can be used as an adsorbent for adsorbing heavy metal ions in sewage. The preparation process is simple and convenient, conditions are easy to control, the waste chlorine-containing plastic or rubber is converted into a functional carbon material with application value and high additional value, and the functional carbon material has good application in the aspects of photocatalysis and heavy metal ion adsorption.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a hydrothermal carbon material by utilizing chlorine-containing plastic or rubber and application thereof, belonging to the technical field of organic waste resource recycling. Background Art

[0002] Polyvinyl chloride (PVC for short) has a structure of (CH2-CHCl) n , polyvinyl chloride has two types: hard and soft. Hard polyvinyl chloride is used for building pipes, making plastic bottles, packaging, etc. Adding plasticizers can make polyvinyl chloride softer and more flexible. It can be used for pipes, cable insulation, etc. In addition, chlorine-containing plastics include polyvinylidene chloride (PVDC), chlorinated polyethylene (CPE), cross-linked polyvinyl chloride, chlorosulfonated polyethylene, chlorinated rubber, chloroprene rubber, etc. Due to the large-scale use of chlorine-containing polymers, chlorine-containing plastic waste is generated. Landfill treatment produces chlorine-containing organic matter, which leads to soil pollution. Incineration treatment produces a large amount of chlorine-containing toxic and harmful gases that pollute the atmosphere.

[0003] Zhao Peitao used NaOH to dechlorinate polyvinyl chloride under hydrothermal conditions (Appl. Sci. 2017, 7, 256). Yoshiei Kato used hot water vapor and oxide catalysts / adsorbents (such as CaO, etc.) to treat polyvinyl chloride to obtain organic chlorine-containing substances and inorganic chlorides (such as CaCl2, CaCl(OH) and Ca(OH)2, etc.) (Polymer Degradation and Stability 2020, 179, 109225). Hong Lan co-pyrolyzed a mixture of Fe3O4 and polyvinyl chloride at 1373 K to obtain a mixture of polyenes and Fe3O4 / Fe2O3 residues, but a small amount of HCl gas was generated (Waste Management 2021, 126, 832–842). However, the above methods inevitably convert polyvinyl chloride into inorganic chlorine, and inorganic bases need to be added as catalysts or dechlorination adsorbents during the conversion process. The resulting solid products are complex and difficult to use effectively.

[0004] Therefore, there is an urgent need to develop a green, pollution-free, simple, easy, fast and efficient method for comprehensively utilizing carbon species in waste chlorine-containing plastics or rubbers and recovering chloride ions. Summary of the invention

[0005] Aiming at the problem that waste chlorine-containing plastics or rubbers are difficult to recycle and cause environmental pollution during landfill and incineration, the present invention provides a method and application of preparing hydrothermal carbon materials and recovering chloride ions by microwave-assisted rapid hydrothermal treatment of waste chlorine-containing plastics.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions: A method for preparing a hydrothermal carbon material using chlorine-containing plastic or rubber: in a closed container, the chlorine-containing plastic or rubber is dispersed in water by ultrasonic dispersion to form a solid-liquid dispersion slurry, which is then transferred to a microwave high-pressure reactor and hydrothermally treated to obtain a hydrochloric acid solution and a hydrothermal carbon material.

[0007] The chlorine-containing plastic or rubber is preferably waste chlorine-containing plastic or rubber.

[0008] The chlorine-containing plastic or rubber is selected from polyvinyl chloride, polyvinylidene chloride, chlorinated polyethylene, cross-linked polyvinyl chloride, chlorosulfonated polyethylene, chlorinated rubber, and chloroprene rubber. The mass ratio of the chlorine-containing plastic or rubber to the volume of water is R , R The range is 0.005~0.5 g / ml.

[0009] The microwave high pressure reactor is a microwave high pressure intermittent reactor or a microwave high pressure continuous flow reactor. The power of the microwave high pressure reactor is 500-2000 W, the reaction temperature is 120-220° C., and the reaction pressure is 0.1-4 MPa.

[0010] The hydrothermal carbon material prepared by the above method is used as a photocatalyst for preparing hydrogen peroxide by oxygen reduction, hydrogen evolution by water reduction, or carbon monoxide by photocatalytic carbon dioxide reduction. It can also be used in heavy metal ion adsorption.

[0011] The photocatalytic reaction is carried out in deionized water. The catalyst can be suspended in the reaction system, or coated on a carrier that does not absorb visible light and ultraviolet light (such as a quartz sheet). The photocatalytic reaction can be carried out in a quartz tube or in a fixed bed reactor. The reaction gas enters the device by bubbling, or in the form of a gas-liquid two-phase mixture. The photocatalytic reaction is carried out in the ultraviolet visible light range, and the light source includes sunlight or artificial light source (such as xenon lamp, LED, tungsten lamp, mercury lamp, etc.).

[0012] The metal ion adsorption experiment is carried out in an aqueous solution containing heavy metal ions. The adsorbent is suspended in the adsorption system and stirred. The removal efficiency of heavy metals is evaluated by measuring the adsorption amount under a certain contact time.

[0013] The present invention aims at the environmental pollution caused by the landfill and incineration of waste chlorine-containing plastics or rubber, and develops a method for degrading waste chlorine-containing plastics or rubber using microwaves. Compared with the prior art, the present invention has the following advantages: (1) the chlorine element is removed from the chlorine-containing plastics or rubber by microwave hydrothermal treatment, thereby effectively avoiding the release of toxic and harmful chlorine-containing gases during the pyrolysis process; (2) the obtained material, as a catalyst and adsorbent, exhibits excellent photocatalytic and adsorption properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 TEM image of Example 1; Figure 2 The UV-Vis-NIR absorption spectrum of Example 1; Figure 3 The UV-Vis-NIR absorption spectrum of Example 3. DETAILED DESCRIPTION

[0015] Below in conjunction with specific embodiment of the present invention, technical scheme of the present invention is clearly and completely described, it is obvious that described embodiment is only a part of embodiment of the present invention, rather than whole embodiment. The reagent, method and equipment adopted in the present invention are conventional reagents, methods and equipment in the art. Based on the embodiment in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work premise belong to the scope of protection of the present invention. Example 1

[0016] Disperse 1 g of waste polyvinyl chloride in 20 mL of deionized water, and ultrasonically disperse the mixture for 10 min to form a solid-liquid dispersion slurry. Transfer the slurry to a 50 mL microwave reaction tank for microwave-assisted hydrothermal treatment. The microwave power is 500 W, the reaction temperature is 160 ° C, the reaction pressure is 1.2 MPa, and the reaction time is 20 min. After the reaction is completed, it is naturally cooled to room temperature, the solid is separated by centrifugation, washed with water and ethanol three times each, and dried at 80 ° C for 24 h to obtain a hydrothermal carbon material. Its morphology is a lamellar structure ( Figure 1 ), and has good light absorption performance in the UV-visible-near infrared region ( Figure 2 ). In addition, the liquid phase after hydrothermal treatment is a hydrochloric acid aqueous solution with a concentration of 0.761 mol∙L -1 , the corresponding dechlorination efficiency is 95%. Example 2

[0017] This embodiment is a comparative example of Example 1, and the difference is that hydrothermal treatment is used without microwave assistance. Specifically, 1g of waste polyvinyl chloride is dispersed in 20 mL of deionized water, and the mixture is ultrasonically dispersed for 10 min to form a solid-liquid dispersion slurry. The slurry is transferred to a 50 mL hydrothermal reaction tank and hydrothermally treated in an oven. The reaction temperature is 160°C, the reaction pressure is 1.2 MPa, and the reaction time is 20 min. After the reaction is completed, it is naturally cooled to room temperature, the solid is separated by centrifugation, washed with water and ethanol three times each, and dried at 80°C for 24 h. The solid phase is still polyvinyl chloride, and no hydrochloric acid is produced in the liquid phase. Example 3

[0018] This embodiment is a comparative example of Embodiments 1 and 2, and the difference is that NaOH is added in the hydrothermal treatment, and the reaction time is prolonged, but there is no microwave assistance. Specifically, 1 g of waste polyvinyl chloride is dispersed in 20 mL of deionized water, and the mixture is ultrasonically dispersed for 10 min to form a solid-liquid dispersion slurry. The slurry is transferred to a 50 mL hydrothermal reaction tank and 0.5 g of NaOH is added. The hydrothermal treatment is carried out in an oven. The reaction temperature is 160°C, the reaction pressure is 1.2 MPa, and the reaction time is 72 h. After the reaction is completed, it is naturally cooled to room temperature, the solid is separated by centrifugation, washed with water and ethanol three times each, and dried at 80°C for 24 h. The solid phase is a hydrothermal carbon material, and the liquid phase is a solution containing sodium chloride, in which the chloride ion concentration is 0.769 mol∙L -1 , the corresponding dechlorination efficiency is 96%. Example 4

[0019] 0.5 g of waste polyvinyl chloride was dispersed in 100 mL of deionized water, and the mixture was ultrasonically dispersed for 20 min to form a solid-liquid dispersion slurry. The solid-liquid dispersion slurry was transferred to a microwave reaction tank and heated at 0.5 mL∙min -1 The flow rate was pumped into an engineering plastic reaction coil system with a diameter of 1 mm and a length of 10 m, and assisted hydrothermal treatment was carried out in a microwave high-pressure continuous flow reactor. The reaction was carried out at 180°C and a reaction pressure of 2.0 MPa in a microwave high-pressure reactor under the condition of a microwave power of 1000 W, and the residence time of the slurry in the reactor was 15.7 min. After the reaction was completed, it was naturally cooled to room temperature, the solid was separated by centrifugation, washed with water and ethanol three times each, and dried at 90°C for 20 h. The solid phase can be directly used as a photocatalyst, and hydrochloric acid is produced in the liquid phase, which can be further utilized. The time to complete the reaction of 100 mL of slurry is 200 min. The liquid phase after hydrothermal treatment is a hydrochloric acid aqueous solution with a concentration of 0.075 mol∙L -1 , the corresponding dechlorination efficiency is 94%. Example 5

[0020] 1 g of waste polyvinylidene chloride was dispersed in 10 mL of deionized water, and the mixture was ultrasonically dispersed for 30 min to form a solid-liquid dispersion slurry. The slurry was transferred to a 100 mL microwave reaction tank for microwave-assisted hydrothermal treatment. The microwave power was 1500 W, the reaction temperature was 200 °C, the reaction pressure was 3 MPa, and the reaction time was 10 min. After the reaction was completed, it was naturally cooled to room temperature, the solid was separated by centrifugation, washed with water and ethanol three times each, and dried at 100 °C for 15 h. The solid phase can be directly used as a photocatalyst, and hydrochloric acid is produced in the liquid phase, which can be further utilized. The liquid phase after hydrothermal treatment is a hydrochloric acid aqueous solution with a concentration of 1.514 mol∙L -1 , the corresponding dechlorination efficiency is 94.5%. Example 6

[0021] Disperse 10 g of waste polyvinyl chloride in 100 mL of deionized water, and ultrasonically disperse the mixture for 40 min to form a solid-liquid dispersion slurry. Transfer the slurry to a microwave reaction tank and heat it at 1 mL∙min -1 The flow rate was pumped into an engineering plastic reaction coil system with a diameter of 1 mm and a length of 10 m, and auxiliary hydrothermal treatment was carried out in a microwave high-pressure continuous flow reactor. The reaction was carried out under the conditions of 1700 W microwave power, 210 ° C in the microwave high-pressure reactor, and the reaction pressure was 1.6 MPa. The residence time of the slurry in the reactor was 7.85 min. After the reaction was completed, it was naturally cooled to room temperature, the solid was separated by centrifugation, washed with water and ethanol three times each, and dried at 110 ° C for 10 h. The solid phase can be directly used as a photocatalyst, and hydrochloric acid is produced in the liquid phase, which can be further utilized. The time to complete the reaction of 100 mL slurry is 100 min. The liquid phase after hydrothermal treatment is a hydrochloric acid aqueous solution with a concentration of 1.498 mol∙L -1 , the corresponding dechlorination efficiency is 93.5%. Example 7

[0022] 1 g of waste chlorinated polyethylene was dispersed in 15 mL of deionized water, and the mixture was ultrasonically dispersed for 50 min to form a solid-liquid dispersion slurry. The slurry was transferred to a 100 mL microwave reaction tank for microwave-assisted hydrothermal treatment. The microwave power was 2000 W, the reaction temperature was 220 ° C, the reaction pressure was 4 MPa, and the reaction time was 1 min. After the reaction was completed, it was naturally cooled to room temperature, the solid was separated by centrifugation, washed with water and ethanol three times each, and dried at 120 ° C for 4 h. The solid phase can be directly used as a photocatalyst, and hydrochloric acid is produced in the liquid phase, which can be further utilized. The liquid phase after hydrothermal treatment is a hydrochloric acid aqueous solution with a concentration of 1.238 mol∙L -1 , the corresponding dechlorination efficiency is 92.7%. Example 8

[0023] Disperse 1 g of waste polyvinyl chloride in 100 mL of deionized water, and ultrasonically disperse the mixture for 60 min to form a solid-liquid dispersion slurry. Transfer the slurry to a microwave reaction tank and heat it at 5 mL∙min. -1 The flow rate was pumped into an engineering plastic reaction coil system with a diameter of 1 mm and a length of 10 m, and auxiliary hydrothermal treatment was carried out in a microwave high-pressure continuous flow reactor. Under the conditions of microwave power of 800 W, the reaction was carried out at 120°C and reaction pressure of 0.1MPa in the microwave high-pressure reactor, and the residence time of the slurry in the reactor was 1.6 min. After the reaction was completed, it was naturally cooled to room temperature, the solid was separated by centrifugation, washed with water and ethanol three times each, and dried at 105°C for 8 h. The solid phase can be directly used as a photocatalyst, and hydrochloric acid is produced in the liquid phase, which can be further utilized. The time to complete the reaction of 100 mL slurry is 20 min. The liquid phase after hydrothermal treatment is a hydrochloric acid aqueous solution with a concentration of 0.145 mol∙L -1 , the corresponding dechlorination efficiency is 90.3%. Example 9

[0024] 5 g of waste cross-linked polyvinyl chloride was dispersed in 50 mL of deionized water, and the mixture was ultrasonically dispersed for 45 min to form a solid-liquid dispersion slurry. The slurry was transferred to a 200 mL microwave reaction tank for microwave-assisted hydrothermal treatment. The microwave power was 1200 W, the reaction temperature was 190 °C, the reaction pressure was 1.5 MPa, and the reaction time was 5 min. After the reaction was completed, it was naturally cooled to room temperature, the solid was separated by centrifugation, washed with water and ethanol three times each, and dried at 85 °C for 18 h. The solid phase can be directly used as a photocatalyst, and hydrochloric acid is produced in the liquid phase, which can be further utilized. The liquid phase after hydrothermal treatment is a hydrochloric acid aqueous solution with a concentration of 1.461 mol∙L -1 , the corresponding dechlorination efficiency is 91.2%. Example 10

[0025] 4 g of waste chlorosulfonated polyethylene was dispersed in 50 mL of deionized water, and the mixture was ultrasonically dispersed for 35 min to form a solid-liquid dispersion slurry. The slurry was transferred to a 100 mL microwave reaction tank for microwave-assisted hydrothermal treatment. The microwave power was 1300 W, the reaction temperature was 150 °C, the reaction pressure was 0.8 MPa, and the reaction time was 18 min. After the reaction was completed, it was naturally cooled to room temperature, the solid was separated by centrifugation, washed with water and ethanol three times each, and dried at 95 °C for 17 h. The solid phase can be directly used as a photocatalyst, and hydrochloric acid is produced in the liquid phase, which can be further utilized. The liquid phase after hydrothermal treatment is a hydrochloric acid aqueous solution with a concentration of 1.154 mol∙L -1, the corresponding dechlorination efficiency is 90%. Embodiment 11

[0026] 1.5 g of waste chlorinated rubber was dispersed in 50 mL of deionized water, and the mixture was ultrasonically dispersed for 25 min to form a solid-liquid dispersion slurry. The slurry was transferred to a 100 mL microwave reaction tank for microwave-assisted hydrothermal treatment. The microwave power was 700 W, the reaction temperature was 130 °C, the reaction pressure was 2.3 MPa, and the reaction time was 14 min. After the reaction was completed, it was naturally cooled to room temperature, the solid was separated by centrifugation, washed with water and ethanol three times each, and dried at 115 °C for 9 h. The solid phase can be directly used as a photocatalyst, and hydrochloric acid is produced in the liquid phase, which can be further utilized. The liquid phase after hydrothermal treatment is a hydrochloric acid aqueous solution with a concentration of 0.447 mol∙L -1 , the corresponding dechlorination efficiency is 92.9%. Example 12

[0027] 0.75 g of waste chloroprene rubber was dispersed in 50 mL of deionized water, and the mixture was ultrasonically dispersed for 55 min to form a solid-liquid dispersion slurry. The slurry was transferred to a 100 mL microwave reaction tank for microwave-assisted hydrothermal treatment. The microwave power was 1900 W, the reaction temperature was 260 ° C, the reaction pressure was 3.8 MPa, and the reaction time was 2 min. After the reaction was completed, it was naturally cooled to room temperature, the solid was separated by centrifugation, washed with water and ethanol three times each, and dried at 105 ° C for 22 h. The solid phase can be directly used as a photocatalyst, and hydrochloric acid is produced in the liquid phase, which can be further utilized. The liquid phase after hydrothermal treatment is a hydrochloric acid aqueous solution with a concentration of 0.224 mol∙L -1 , the corresponding dechlorination efficiency is 93.4%. Example 13

[0028] 3.6 g of waste polyvinyl chloride was dispersed in 120 mL of deionized water, and the mixture was ultrasonically dispersed for 60 min to form a solid-liquid dispersion slurry. The slurry was transferred to a 200 mL microwave reaction tank for microwave-assisted hydrothermal treatment. The microwave power was 1600 W, the reaction temperature was 170 ° C, the reaction pressure was 2.8 MPa, and the reaction time was 12 min. After the reaction was completed, it was naturally cooled to room temperature, the solid was separated by centrifugation, washed with water and ethanol three times each, and dried at 115 ° C for 7 h. The solid phase can be directly used as a photocatalyst, and hydrochloric acid is produced in the liquid phase, which can be further utilized. The liquid phase after hydrothermal treatment is a hydrochloric acid aqueous solution with a concentration of 0.452 mol∙L -1 , and the corresponding dechlorination efficiency is 94.1%. Embodiment 14

[0029] 25 mg of the solid product of Examples 1 to 13 and 50 mL of deionized water were added to a quartz tube, and oxygen was continuously introduced, a 300 W LED lamp was turned on, and the mixture was fully stirred for 1 h under illumination. After the reaction was completed, the concentration of hydrogen peroxide in the liquid was tested. The photocatalyst generated by the technical solution has a good hydrogen peroxide generation effect. As a comparative example, Example 2 did not show the performance of photocatalytic synthesis of hydrogen peroxide, and the photocatalytic performance of Example 3 was poor.

[0030] Embodiment 15

[0031] 50 mg of the solid product in Examples 1 to 13 and 100 mL of deionized water were added to a quartz tube, and carbon dioxide was introduced. A 300 W LED lamp was turned on, and the mixture was fully stirred for 1 h under illumination. The gas product was collected for testing. The photocatalyst generated by the technical solution had a good carbon dioxide reduction effect. As a comparative example, Example 2 did not show the performance of photocatalytic carbon dioxide reduction, and the photocatalytic performance of Example 3 was poor.

[0032]

[0033] Example 16 50 mg of the solid product in Examples 1 to 13 was added to a quartz tube containing 90 ml of deionized water and 10 ml of triethanolamine, and argon was continuously introduced to exhaust the gas in the reactor, and a 300 W LED lamp was turned on, and the mixture was fully stirred for 1 h under illumination. After the reaction was completed, the gas product was collected and tested. The photocatalyst generated by this technical solution has a good hydrogen production effect. As a comparative example, Example 2 did not show the performance of photocatalytic hydrogen production, and the photocatalytic performance of Example 3 was poor.

[0034]

[0035] Embodiment 17 Cd(NO3)2·4H2O or Cu(NO3)2·3H2O was dissolved in water to prepare 2+ or Cu 2+ In a typical adsorption experiment, 50 mg of the solid products in Examples 1 to 13 were added to 200 mL of 500 mg·L -1 Cd 2+ or Cu 2+The metal solution was stirred at a speed of 500 rpm. The removal efficiency of heavy metals was quantified by measuring the adsorption amount at a contact time of 30 min. As a comparative example, Example 2 showed almost no adsorption performance for heavy metal ions, and Example 3 had poor adsorption performance.

[0036]

Claims

1. A method for preparing a hydrothermal carbon material using chlorine-containing plastic or rubber, characterized in that: In a closed container, chlorine-containing plastic or rubber is dispersed in water by ultrasonic dispersion to form a solid-liquid dispersion slurry, which is then transferred to a microwave high-pressure reactor and hydrothermally treated to obtain a hydrochloric acid solution and a hydrothermal carbon material.

2. The method for preparing hydrothermal carbon material using chlorine-containing plastic or rubber according to claim 1, characterized in that: The chlorine-containing plastic or rubber is waste chlorine-containing plastic or rubber.

3. The method for preparing hydrothermal carbon material using chlorine-containing plastic or rubber according to claim 1, characterized in that: The chlorine-containing plastic or rubber is selected from polyvinyl chloride, polyvinylidene chloride, chlorinated polyethylene, cross-linked polyvinyl chloride, chlorosulfonated polyethylene, chlorinated rubber, and chloroprene rubber.

4. The method for preparing hydrothermal carbon material using chlorine-containing plastic or rubber according to claim 3, characterized in that: The mass ratio of chlorine-containing plastic or rubber to the volume of water is R , R The range is 0.005~0.5 g / ml.

5. The method for preparing hydrothermal carbon material using chlorine-containing plastic or rubber according to claim 1, characterized in that: The microwave high-pressure reactor is a microwave high-pressure intermittent reactor or a microwave high-pressure continuous flow reactor.

6. The method for preparing hydrothermal carbon material using chlorine-containing plastic or rubber according to claim 5, characterized in that: The power of the microwave high-pressure reactor is 500~2000 W, the reaction temperature is 120~220℃, and the reaction pressure is 0.1~4 MPa.

7. The hydrothermal carbon material prepared by the method according to any one of claims 1 to 6.

8. The hydrothermal carbon material according to claim 7 is used as a photocatalyst for the reduction of oxygen to produce hydrogen peroxide, or the reduction of water to produce hydrogen, or the photocatalytic reduction of carbon dioxide to produce carbon monoxide.

9. Use of the hydrothermal carbon material according to claim 7 in the adsorption of heavy metal ions.